2016
DOI: 10.1097/dcc.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chlorhexidine Use to Prevent Ventilator-Associated Pneumonia in Adults

Abstract: Ventilator-associated pneumonia (VAP) describes pneumonia in patients requiring mechanical ventilation that was not present prior to intubation. Ventilator-associated pneumonia concurrently increases patient mortality, hospital length of stay, and health care costs. Ventilator-associated pneumonia also contributes to patient morbidity, which is challenging the progression of patient care in intensive care units throughout the United States. Through critique of current literature, suitable interventions for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…Many studies have shown the effectiveness of oral hygiene management, including the application of CHX, for respiratory disease prevention in ICU patients [6,11,21,41,47,48,51,53,54,56,60,61,[67][68][69][70][71][72][73][74][75][76]. In 2013, Hillier et al reported that the education of nurses on oral care, including CHX application and other oral care methods, reduced the incidence of VAP [3].…”
Section: Outcomes Of Oral Management Of Icu Patientsmentioning
confidence: 99%
“…Many studies have shown the effectiveness of oral hygiene management, including the application of CHX, for respiratory disease prevention in ICU patients [6,11,21,41,47,48,51,53,54,56,60,61,[67][68][69][70][71][72][73][74][75][76]. In 2013, Hillier et al reported that the education of nurses on oral care, including CHX application and other oral care methods, reduced the incidence of VAP [3].…”
Section: Outcomes Of Oral Management Of Icu Patientsmentioning
confidence: 99%
“…In support of the relevance of these findings, improving oral hygiene and cleansing in at risk patients (ICU patients and elderly) have been advocated to prevent the occurrence of aspiration pneumonia, hospital-acquired pneumonia (HAP), and VAP. The use of chlorhexidine mouthwash reduces the risk of developing VAP but did not show mortality benefit [41,42]. However, all results examining this issue do not show consensus in the conclusions.…”
Section: Dysbiosis In Acute Respiratory Tract Infectionsmentioning
confidence: 95%
“…Solutions for oral care may use chlorhexidine, saline solution, and purified water. Studies showed that even a concentration of 0.12% to 0.2% chlorhexidine was still effective for prevention of VAP (Ames et al., 2011; Liao et al., 2015; Needleman et al., 2011; Zuckerman, 2016). Third, the frequency of oral care varied between different studies.…”
Section: Literature Reviewmentioning
confidence: 99%